2020
DOI: 10.1002/lsm.23319
|View full text |Cite
|
Sign up to set email alerts
|

Pixel CO2 Laser for the Treatment of Stress Urinary Incontinence: A Prospective Observational Multicenter Study

Abstract: Background and Objectives Energy‐based treatments have been found to be a promising treatment modality for improving stress urinary incontinence (SUI) symptoms. This prospective two‐center study was designed to evaluate the efficacy of fractional‐pixel CO2 laser for the treatment of SUI. Study Design/Materials and Methods Eighty‐five women with SUI symptoms as per the cough stress test and validated International Consultation on Incontinence Questionnaire—Urinary Incontinence Short Form (ICIQ‐UI‐SF), were trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…A total of 114 papers were included according to the eligibility criteria listed above. Of these, 111 studies investigated GSM, VVA, UI, and LS symptoms as primary indication (Tables 3–6); 15 RCT, 23–37 87 cohort studies, 38–124 eight case reports, 125–132 one case‐control study, 133 including a total of 9000 women, not accounting for overlap between the studies. Additionally, three cross‐sectional studies focused solely on the characteristics of AEs 134–136 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 114 papers were included according to the eligibility criteria listed above. Of these, 111 studies investigated GSM, VVA, UI, and LS symptoms as primary indication (Tables 3–6); 15 RCT, 23–37 87 cohort studies, 38–124 eight case reports, 125–132 one case‐control study, 133 including a total of 9000 women, not accounting for overlap between the studies. Additionally, three cross‐sectional studies focused solely on the characteristics of AEs 134–136 .…”
Section: Resultsmentioning
confidence: 99%
“…Of the included studies, 81 studies investigated CO 2 ‐LASER from different manufacturers 23–31,33,35,36,38–58,66–93,95–104,122–125,128–131,133,136 . Twenty‐eight studies investigated Er:YAG LASER from different manufacturers 32,34,59–65,94,107–121,127,132,135 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous case series have demonstrated mixed results regarding the potential efficacy of laser therapy for treating pelvic organ prolapse, genitourinary syndrome of menopause and sexual function, and several studies that utilized sub-optimal methodology have demonstrated mixed results regarding the potential efficacy of CO 2 laser for treatment of SUI [ 10 17 ]. The main flaw of most studies regarding laser use for benign gynecological indications is the prominent lack of a control or sham group.…”
Section: Introductionmentioning
confidence: 99%